(untitled) (Global Journal of Management and Business Research, 2014)
The main aims of this study to investigate the impact of the determinant of portfolio return performance during and post finical market crisis based on the most active firms listed on Amman Stock Exchange (ASE) for the period from 2008 to 2012 has been studied. In this study, using the framework of the Capital Assets Pricing Model (CAPM) as considered to be a centrepiece in optimal portfolio determinants. An important contribution of this framework is that it allows to derive optimal portfolio implications for economies in which the degree of correlation across different finical sectors. The test data set is the monthly prices based on 59 samples of the most active companies. This empirical study proposed that this is not a normal cyclical crisis of capitalism but a global crisis, which requires a change in the management policy to be tackled with new regulatory frameworks for financial institutions in order to stimulate economic activities.